STUDI DESKRIPTIF PENINGKATAN KUALITAS PENGGUNAAN BUKU KIA PADA IBU BALITA DI DESA KALIBAGOR - Siti Nurhayati; Colti Sistiarani; Endo Dardjito (Kesmas Indonesia, 2014)
ABSTRACTMaternal and Child Health ( MCH ) as a means of recording maternal and child health services since pregnant women, childbirth and during the postpartum infants born to 5 years old, including service family planning, immunization, nutrition and child development. Some issues related to the use of the MCH book are: completeness of data entry in the MCH book, the quality of the data recorded in the book of MCH, and the level of compliance of the mother carrying the MCH book . The purpose of this activity is to improve maternal compliance in carrying the book when visiting post integrated community.This study is to monitor compliance with the mother in bringing continuous MCH book every month for about 2 months . This indicator is observed / checked to the mother during a visit to a neighborhood health center before the intervention and after implementation of the intervention on each posyandu organizing activities that serve as research sites / partners . From the observation of no increased adherence posyandu Puspitasari toddler 's mother after giving intervention IEC, from 56.6 % to 60 % ( increase of 3.4 % ). Increased compliance posyandu watugede toddler 's mother after giving IEC intervention is of 33.3 % to 50 % ( an increase of 16.7 % ) . Suggested to always deliver IEC moms toddlers in posyandu so bring a book MCH compliance is maintained. IEC can be given by health professionals or by a health worker.Keyword: Mathernal and Child Health (MCH) book, Information, Education and Communication (IEC). Kesmasindo, Volume 7( 1) Juli 2014, Hal 54-62